Spiked Nanostructures Disrupt Fungal Biofilm and Impart Increased Sensitivity to Antifungal Treatment (Adv. Mater. Interfaces 12/2022). Issue 12 (22nd April 2022) - Hayles, Andrew; Bright, Richard; Wood, Jonathan; Palms, Dennis; Zilm, Peter; Brown, Toby; Barker, Dan; Vasilev, Krasimir
Abstract : Antimicrobial Surface with Sharp Protrusions In article number 2102353, Andrew Hayles, Krasimir Vasilev, and co‐workers demonstrate that fungal pathogens experience severe cell wall stress and impeded hyphae formation when incubated on nanostructured antimicrobial surfaces. This results in disrupted biofilms which are markedly more sensitive to antifungal drugs at subclinical concentrations. Amphotericin B entirely eradicates C. albicans on the nanostructured surface while failing to clear cells on the smooth control.